Factors affecting organic rice production adoption of farmers in Northern Thailand - Pattana Jierwiriyapant (2018)
Recent health concerns have resulted in the increased demand for organic foods in both develop and developing countries. This situation was believed to give farmers an opportunity to receive bigger profits by using organic methods. The aim of this paper is to reflect on the main factors that influence farmers in northern Thailand to begin producing organically grown rice. The surveys and in-depth interviews reveal that, the number of farmers who have adopted organic rice-growing methods is small, but has been rapidly increasing since 2008. The results from this study show that influence of training can be found to be an important decision-making factor for northern Thai farmers who decide to adopt organic rice-growing methods. Farmers who switch to organic farming join organic agricultural networks in order to have stronger market security and receive further training. It was also found that factors that influenced the farmers' decisions to apply organic agricultural methods are their concerns for their own health, followed by the success of neighboring organic farms, excellent export opportunities and continued support from their agricultural network, respectively. Economic factors were also in play such as access to high quality organic rice seed, the low costs of production, guaranteed higher buying prices than non-organic rice and access to buyers through agricultural networks. In addition, having control over the land and water supply were also cited as physical and biological influencing factors.